(untitled) (BIRDEM Medical Journal, 2020)
Prolonged steroid use and the resultant adrenal insufficiency pose an increased risk of severe disease in patients with COVID-19. We describe here a case of Covid-19 with adrenal crisis in an elderly man at a semiurban primary healthcare center. He and his family were forced to leave their home because of being infected with SARS-CoV-2. He was managed for adrenal crisis at a limited resource setting with a good outcome. This case also highlights the importance of social stigma related to COVID-19 in Bangladesh. Birdem Med J 2020; 10, COVID Supplement: 122-126